Profiling and compaction behavior of a slope-adaptive system for cross-slope no-till planting: Simulation and field insights - Li, Hang; He, Jin; Chu, Huilong; Li, Hongwen; Wang, Qingjie; Wang, Chao; Li, Yunpeng; Meng, Ziqing (International Journal of Agricultural and Biological Engineering, 2026)
To enhance the operational stability and adaptability of soil-covering and compaction devices during no-till seeding on sloped farmland, this study developed a DEM–MBD coupled simulation model suited for conditions involving real-time slope variation and applied it to the design and analysis of a slope-adaptive covering–compacting device (SACCD). By coupling multi-body dynamics with the discrete element method, the model simulated the motion behavior and soil interaction process of the SACCD under different slope change rates, revealing its asynchronous response characteristics and profiling compaction mechanisms during dynamic slope transitions. Field experiments further verified the device’s performance and the accuracy of the simulation. At the Lishu test site, the SACCD achieved a coefficient of variation of soil compaction of 20.4% under an average surface slope variation rate of 0.087 rad/s. At the Keshan test site, the coefficient of variation of soil compaction was 18.9%, with an almost constant slope. The differences between simulation and field results for the coefficient of variation of soil compaction were 8.32% (Lishu) and 1.02% (Keshan), confirming the reliability of the model and the rationality of the SACCD structural design. Overall, the simulation and field results demonstrate that the SACCD can maintain effective profiling posture and compaction performance under dynamic slope variation, providing a feasible approach and theoretical basis for the design and performance prediction of soil-covering and compaction devices for complex sloped farmland. Keywords: variable slope, cross-slope, slope-adaptive, compaction, DEM-MBD DOI: 10.25165/j.ijabe.20261901.10094 Citation: Li H, He J, Chu H L, Li H W, Wang Q J, Wang C, et al. Profiling and compaction behavior of a slope-adaptive system for cross-slope no-till planting: Simulation and field insights. Int J Agric & Biol Eng, 2026; 19(1): 67–75.